Historical Analysis of Climate Change and Agriculture Events in the SADC Region 1970-2020 - Chesterman, Sabrina; Neely, Constance; Gosling, Amanda (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Historical analysis in foresight planning involves looking at what has happened over a relevant, prescribed timeline to try to understand why current and future patterns are emerging. This is done by reviewing relevant events, stakeholders involved, processes, and patterns that occur within the chosen historical time frame. Any recent history relevant to the focal issue is assessed for its potential continuation into the future, essentially providing a temporal bridge. For the purposes of this analysis, the historical time frame selected as relevant to the theme of climate-resilient agri-food systems in the SADC region is 50 years (1970- 2020). The topics chosen for analysis include the external systems or drivers of change likely to impact the future productivity of regional agri-food systems, namely climate change (droughts and flooding), agricultural pests and diseases, human health, trade, political past, and conflict. The timelines show the years that relevant events took place and the magnitudes of their impacts e.g. the number of human lives lost.